Management analysis of dairy cow herd enterprises in the Kansas Farm Management Association - DeLano, F.D.; Langemeier, Michael R. (Kansas Agricultural Experiment Station, 2011)
Actual records of dairy cow herd enterprises from Kansas Farm Management Association farms over the past 4 years have shown an increase in returns over variable costs from $17,900 to $27,000 per farm for a 100-cow dairy herd in favor of herds with higher milkproducing cows. Cost per hundred weight of milk produced per cow decreased for the higher-producing herds compared with lowerproducing herds, even though total cost per cow increased. In 1993, for every extra $1.00 spent on feed and other variable costs, the higher producing herds earned $2.34. This was a 234% return per dollar invested.
Typo of author's name M. L. Langemeier; should be M. R. Langemeier.
Keywords: Economics; Dairy; Management